Validation of New Cancer Biomarkers: A Position Statement from the European Group on Tumor Markers. (6th January 2020) - Duffy, Michael J; Sturgeon, Catharine M; Sölétormos, György; Barak, Vivian; Molina, Rafael; Hayes, Daniel F; Diamandis, Eleftherios P; Bossuyt, Patrick M M
Abstract: BACKGROUND: Biomarkers are playing increasingly important roles in the detection and management of patients with cancer. Despite an enormous number of publications on cancer biomarkers, few of these biomarkers are in widespread clinical use. CONTENT: In this review, we discuss the key steps in advancing a newly discovered cancer candidate biomarker from pilot studies to clinical application. Four main steps are necessary for a biomarker to reach the clinic: analytical validation of the biomarker assay, clinical validation of the biomarker test, demonstration of clinical value from performance of the biomarker test, and regulatory approval. In addition to these 4 steps, all biomarker studies should be reported in a detailed and transparent manner, using previously published checklists and guidelines. Finally, all biomarker studies relating to demonstration of clinical value should be registered before initiation of the study. SUMMARY: Application of the methodology outlined above should result in a more efficient and effective approach to the development of cancer biomarkers as well as the reporting of cancer biomarker studies. With rigorous application, all stakeholders, and especially patients, would be expected to benefit.